TEKNIK GURU PENDIDIKAN AGAMA HINDU DALAM MENCIPTAKAN PEMBELAJARAN BERBASIS PAIKEM DI SMP NEGERI 2 WLINGI-BLITAR, JAWA TIMUR - Sujianto Sujianto (Pascasarjana Universitas Hindu Indonesia, 2017)
PAIKEM-based learning is one of learning designs based on the constructivistic approach. Learning is a process of manifestion of ideas into new experiences. Knowledge is built little by little and the results are expanded through an unlimited context and cannot be constructed abruptly. In the constructivist view, the strategy of gaining knowledge is more precedence over than how many the students remember the knowledge. While the role of the teachers during the learning process is as only as the facilitator who facilitates student in learning by making meaningful and relevant knowledge, giving the students the opportunity to find and apply ideas and awaken the students to apply their strategies during the learning process.